Um Breve Histórico de Conceitos Fundamentais da Estratigrafia Moderna: Sequências Deposicionais e seus Fatores Controladores - HOLZ, MICHAEL (Pesquisas em Geociências, 1998)
Stratigraphy, fundamental to geological science, has been subjected to deep epistemological changes during the last two decades, changes that are generally seen as being a result of the North American school of stratigraphy, specially concerning research groups linked to petroleum geology. However, the fundamentals of modern stratigraphy, such as the concept of depositional sequence and the discussion on its tectonic and eustatic controls, were already discussed and applied in the beginning of the twenthieth century and earlier, and insofar are not product of research of our times, but result of some ideas as old as the ideas of Lyell and Darwin. The present paper presents a brief historical review of stratigraphy’s history during the last hundred and fifty years and discusses the historical roots of fundamental concepts of modern stratigraphy.